Implikasi Yuridis Verifikasi Substantif Dalam system AHU Terhadap Keefektifan Perubahan Data Perseroan Terbatas - Alexandra Kyra Trisno; I Gusti Ayu Apsari Hadi; Jeremiah Imanuel Sianturi (Jurnal Ilmu Hukum Sui Generis, 2025)
Digital transformation in legal administration through the General Legal Administration (AHU) system (AHU System) has driven the modernization of the technical procedures in changing Limited Liability Company data. However, the recent implementation of substantive verification policies by the Ministry of Law via the AHU System is leading to an expansion of the previously limited administrative functions toward a substantive supervision/review of corporate data. This research aims to analyze the compliance of the AHU System substantive verification policies in respect of company data changes with the legal construction of the the Limited Liability Company Law, as well as to examine its implications to the effectiveness of Limited Liability Company data changes. This study uses a normative legal research method with a legislative and conceptual approach. Legal materials were obtained through library research consisting of primary, secondary, and tertiary legal materials, and then systematically analysed using grammatical and systematic interpretation. The research results indicate that substantive verification essentially still falls within the administrative authority framework of the Directorate General of General Legal Administration as an administrative quality control mechanism to maintain the validity and integrity of legal entity data. However, its implementation shows a shift in the character of legal entity administration from administrative recording to administrative substantive control. This shift causes the procedure for changing PT data to become longer and more complex due to additional stages of document inspection and corporate data validity. In practice, issues such as document inconsistencies, data input errors, and unconfirmed shareholder emails have the potential to cause delays in the issuance of notification acceptance letters and Ministerial decisions. This condition affects the effectiveness of administrative services and creates potential administrative uncertainty regarding the status of the company's directors, commissioners, and shareholders.